INTEGRATIVE MULTICULTURALISM IN THE FORMER YUGOSLAVIA - Milosavljevic Stevic, Milena (Political Review, 2025)
The author analyzes the policy and practice of integrative multiculturalism in the former Socialist Federal Republic of Yugoslavia (SFRY), the consequences of which are still noticeable today. The numerous mechanisms that made up the structure of integrative multiculturalism in the former SFRY today represent some of the main goals from which minority groups in Serbia proceed and strive. An analysis of the historical context and the state constitution of the former state of Yugoslavia clearly indicates the existence of the practice of integrative multiculturalism in various forms, which as such represented the state's political response to "diversity", but also a significant ideological and political concept of the ruling elites. Integrative multiculturalism was present starting from the Congress of Berlin (1878) when the provisions on religious freedom were adopted and imposed on the Balkan states - Turkey, Romania, Bulgaria and Serbia, by France, Germany, Austria-Hungary and Italy, through the formation of the First Yugoslavia (1918–1945) or the Kingdom of Serbs, Croats and Slovenes, and then the Second Yugoslavia (1945–1992), the Federal People's Republic of Yugoslavia (FNRJ) which in 1963 changed its name to the Socialist Federal Republic of Yugoslavia (1963–1992), which was followed by a period of interethnic wars in the Yugoslav federation for which integrative multiculturalism is considered responsible.
Keywords: integrative multiculturalism; national groups; nationalism; segregation; national minorities; SFRY